Faktor-Faktor Yang Berhubungan Dengan Pengetahuan Perawat Tentang Perawatan Paliatif Pada Anak Kanker di RS Wilayah Jakarta - Carolina Putri Indah Sari; Lina Dewi Anggraeni; Wilhelmus Hary Susilo (PT. Pubsains Nur Cendekia, 2023)
Pediatric palliative care focuses on providing holistic and integrated care to improve the quality of life for children and adolescents with underlying illnesses. The challenge faced by nurses is to equalize the perception between parents and the medical team in carrying out palliative care. This study aims to determine the factors related to nurses' knowledge about palliative care for children with cancer at hospitals in the Jakarta area. This research used a cross sectional design with a total sampling technique of 47 respondents. The measuring tool used was a nurse knowledge questionnaire about palliative care originating from Abuhammad's research which had been translated and modified by the researcher. Data analysis used SPSS version 25 with the Spearman's rho statistical test which was used to test the strength of the relationship between two variables that were not based on actual data values. The results of the study showed that there was no relationship between age (p = 0.961), last education (p = 0.822), length of work (p = 0.307), skills possessed (p = 0.076), and mastery of work (p = 0.272) with Nurses' knowledge about palliative care. Nurses need to increase their knowledge which can be done by participating in training and education about palliative care, so that they can increase nurses' self-confidence.